The Kink - Burtis, Thomson, 1896-1971 (Salt Lake City, UT : Project Gutenberg, 2024)
"The Kink" by Thomson Burtis is a short story likely written in the early 20th century. This narrative takes place within the context of military aviation, focusing on the experiences of pilots during a transformative period in flight. The central theme revolves around the challenges of aging in the field of aviation and the dynamics between seasoned pilots and younger, more audacious flyers. The story follows Jim Finley, a test pilot who grapples with the realization that he is becoming too old to fly while dealing with the brashness of the younger pilot, Kink Forell. As Finley pilots an outdated aircraft, he reflects on his past glories and the stark contrast to his present situation. The plot thickens as Finley is forced to confront not only his physical limitations after being grounded due to deteriorating vision, but also the reckless behavior of Kink, who refuses to adhere to caution in flying. Their relationship is strained as Kink's arrogance grows, ultimately leading to a life-threatening situation where they must work together to navigate a risky takeoff from a precarious location. The story explores themes of pride, vulnerability, and the harsh realities of retirement from a beloved profession, drawing readers into the high stakes of aviation and the personal struggles of its protagonists. (This is an automatically generated summary.)
Release date is 2024-05-04
Roger Frank and Sue Clark
Keywords: Short stories; Interpersonal relations -- Fiction; Air pilots -- Fiction; United States. Army. Air Service -- Fiction